2015 International Conference on Science in Information Technology (ICSITech) 2015
DOI: 10.1109/icsitech.2015.7407793
|View full text |Cite
|
Sign up to set email alerts
|

Research plan development concerning e-image impact towards online purchase intention and premium pricing strategies in Indonesia community based online market

Abstract: The Gregg and Walczak definition about e-image has been inspired us to examine their theoretical model in a different digital marketplace environment. As a novelty, we introduced the Real-Time Support Assistance (RTOSA) concept as a supplementary moderating variable. This paper constitutes hypothetical development about the proposed RTOSA and contains a brief description of Indonesia largest online community forum that projected as our online experimental research dioramas. This proposed research aims to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The image of the online store helps, among other aspects, to the construction of perception, that is, to organize the concepts that the customer has in his mind in relation to the value offer materialized in the product, which translates into an anticipated preconception of customer satisfaction. Satisfaction of previous expectations that customers have will significantly influence their intention to buy online (51), even when the product in the online store has a higher price than the competition (53) On the other hand, it is confirmed that trust positively influences online purchase intention, so it can be stated that consumers trust a brand that provides them with security, quality and the ability to satisfy their expectations (39) (57). E-trust generates brand loyalty, drives online sales, and influences customer perceived value (41) (55) (58), therefore, the customer can interact comfortably and safely on the virtual platform during the purchase, with the confidence of obtaining the product they expect.…”
Section: Contrasting the Hypothesesmentioning
confidence: 94%
See 2 more Smart Citations
“…The image of the online store helps, among other aspects, to the construction of perception, that is, to organize the concepts that the customer has in his mind in relation to the value offer materialized in the product, which translates into an anticipated preconception of customer satisfaction. Satisfaction of previous expectations that customers have will significantly influence their intention to buy online (51), even when the product in the online store has a higher price than the competition (53) On the other hand, it is confirmed that trust positively influences online purchase intention, so it can be stated that consumers trust a brand that provides them with security, quality and the ability to satisfy their expectations (39) (57). E-trust generates brand loyalty, drives online sales, and influences customer perceived value (41) (55) (58), therefore, the customer can interact comfortably and safely on the virtual platform during the purchase, with the confidence of obtaining the product they expect.…”
Section: Contrasting the Hypothesesmentioning
confidence: 94%
“…The e-image includes the reputation, quality of the information on the web, the performance of the quality of the service and any other factor that represents the image of the company. The e-image or online image, allows the sustainability of a business by generating reliability, credibility and integrity on the part of the company and individuals in an online environment; therefore, a positive e-image favors the decision to purchase a product that may have a higher price than the competition (53). Consequently, the image of an online retail store or the e-tailer image, allows positive associations with the brand, word of mouth marketing and perception of customer value (54), showing that the more positive the image, more notable is the degree of customer satisfaction (55).…”
Section: Imagementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we believe that the presence of retailers in the online channel is also required. Through the electronic Word of Mouth [21], [22] and instant messaging technology for real-time online support assistance [23], [24]. Then, we think that Social Presence in the realm of online transactions is also important to be held.…”
Section: E-commerce Channelmentioning
confidence: 99%